Beyond gene dictation in oral squamous cell carcinoma progression and its therapeutic implications. (6th April 2017) - Kumar, Ajay; Sarode, Sachin C; Sarode, Gargi S; Majumdar, Barnali; Patil, Shankargouda; Sharma, Nilesh Kumar
In recent, mechanisms behind transition from normal epithelium to premalignancy and finally to oral carcinoma have been linked to genetic and epigenetic multistep process. These epigenetic changes are heritable, potentially reversible, and presented as epigenetic signature normal and carcinoma cells. Such epigenetic alterations have been suggested as DNA methylation, histone modifications, and small noncoding RNAs. These extragenetic changes have been reported to play a role in the modulation of several key signaling, regulatory, and repair routes in oral squamous cell carcinoma (OSCC) and other carcinomas. In this review, we summarize scientific developments in the last decade, substantiating the role of extra- and beyond genetic molecular signatures in OSCC progression, and potential biomarker and implications in chemotherapy intervention.